Study Of Pithecellobium Jiringa (Jack) Prain On Carcinogenesis And Angiogenesis Mechanistic Pathway - Muslim, Nahdzatul Syima (2012)
In this work, the anti-tumour potential of P. jiringa fruit rind was investigated. An array of studies was carried out to evaluate its anti-tumour effect and characterised the components at play and the biological target(s) that contribute to the anti-tumour effect. In the first part of this work, a series of solvent extract(s) of the P. jiringa fruit rind namely 100% ethanol (EtOH), 50% ethanol (EW), 50% methanol (MW), 100% methanol (MeOH) and 100% water (Wa) was developed via maceration technique.